Analisis Konsumsi Listrik di Provinsi Papua terhadap Pengaruh Investasi, Belanja Pengeluaran Daerah, Indeks Pembangunan Manusia dan Jumlah Penduduk - Yosef Lefaan; Edwin Ginting; Johni Jonatan Numberi; Endang Hartiningsih; Maran Gultom; Thobby Wakarmamu; Tiper K. M. Uniplaita (Fakultas Teknik Universitas Pancasila, 2023)
Electricity consumption is an important factor in driving economic growth. Increasing economic growth will increase electricity consumption, and vice versa. The effect of the growth of electricity consumption on economic growth in Papua Province is a goal to be known through this research. To achieve this goal, secondary data for 2012–2022, sourced from the Central Bureau of Statistics for Papua Province and PT. PLN (Persero) Papua and West Papua regions, are processed using a quantitative approach and multiple regression analysis model. This secondary data includes investment value, regional expenditure, the human development index, and population, which is an independent variable. While the electricity consumption data is a dependent variable. The results of the study show that simultaneously, all independent variables have a significant effect on the dependent variable. The value of investment, regional expenditures, and the human development index have a positive but not significant effect on increasing electricity consumption. While the population has a positive and significant influence on increasing electricity consumption.